2019
DOI: 10.1016/j.smrv.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia and mortality: A meta-analysis

Abstract: The purpose of this review was to evaluate the strength of evidence for a relationship between risk of mortality and frequent and ongoing insomnia using a meta-analytic strategy. Seventeen studies, including a total of 36,938,981 individuals followed up for a mean of 11.6 years, reporting the investigation of the association between mortality and frequent (≥3 nights/week), ongoing (≥1 month) insomnia were identified. There was no difference in the odds of mortality for those individuals with symptoms of insomn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 57 publications
4
54
1
3
Order By: Relevance
“…Overall, insomnia symptoms were not associated with mortality. When we investigated the influence of each insomnia symptom on mortality risk, stratified by sleep duration, both difficulty initiating sleep (HR 1.51, 95% CI No work, n (%) 4496 (28) 4714 (20) 5406 (29) 3804 (18) 5281 (25) 3929 (22) 4581 (19) 4629 (30) 5718 (23) 3492 (25) Current smokers, n (%) Past smokers, n(%) 3980 (25) 6261 (27) 5019 (27) 5222 (25) 5557 (27) 4684 (26) 6089 (26) 4152 (27) 6431 (26) 3810 (27) BMI 2542 (16) 3665 (16) 2758 (15) 3449 (17) 3230 (15) 2977 (16) 4103 (17) 2104 (14) 4238 (17) 1969 (14) Coffee consumption, number of cups daily (SD) 2.9 (1.8) Depression, n (%) 4674 (29) 3954 (17) 5024 (27) 3604 (17) 5213 (25) 3415 (19) 6675 (28) 1953 (13) 6818 (27) 1810 (13) Cancer diagnosis, n (%) (Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, insomnia symptoms were not associated with mortality. When we investigated the influence of each insomnia symptom on mortality risk, stratified by sleep duration, both difficulty initiating sleep (HR 1.51, 95% CI No work, n (%) 4496 (28) 4714 (20) 5406 (29) 3804 (18) 5281 (25) 3929 (22) 4581 (19) 4629 (30) 5718 (23) 3492 (25) Current smokers, n (%) Past smokers, n(%) 3980 (25) 6261 (27) 5019 (27) 5222 (25) 5557 (27) 4684 (26) 6089 (26) 4152 (27) 6431 (26) 3810 (27) BMI 2542 (16) 3665 (16) 2758 (15) 3449 (17) 3230 (15) 2977 (16) 4103 (17) 2104 (14) 4238 (17) 1969 (14) Coffee consumption, number of cups daily (SD) 2.9 (1.8) Depression, n (%) 4674 (29) 3954 (17) 5024 (27) 3604 (17) 5213 (25) 3415 (19) 6675 (28) 1953 (13) 6818 (27) 1810 (13) Cancer diagnosis, n (%) (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…A pooled analysis of 10 studies that evaluated the association between insomnia and total mortality found that individuals who reported difficulty initiating sleep or non-restorative sleep had an increased and dose-dependent risk of all-cause mortality compared to individuals without these symptoms, 12 whereas a recent meta-analysis of 17 studies investigating the relationship between insomnia and mortality found no association. 13 Lovato and Lack conclude from their meta-analysis that there is a need for studies which combine sleep duration and insomnia symptoms. 14 They also point out the need for longer follow-up times (than the mean follow-up duration of 11.6 years in their meta-analysis), and for consideration of daytime symptoms combined with sleep symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, it has been proposed by Bin that much of these evidence points to connecting sleep duration to physical health, and linking sleep quality to mental health. While several meta-analyses have found significant associations between insomnia and mortality and cardiovascular diseases [10][11][12], there remains a dearth of research looking at the relationship between sleep disturbance and other physical diseases, or that between sleep duration and psychiatric diseases. Secondly, Bin also highlighted that sleep duration and quality have been conceptualized so distinctly that many have failed to recognise that they are measures of the same underlying phenomenon [9].…”
Section: Introductionmentioning
confidence: 99%
“…On average, more than 30% of human life is spent sleeping [1]. Apart from rejuvenation, sleep is directly associated with the proper function of the central nervous system, blood pressure maintenance, metabolism, catabolism, temperature regulation, memory consolidation and several other essential physiological functions [2]. In recent times, Insomnia or sleeplessness has become a common disorder that is affecting a large global population and impairing the general health and mental wellbeing.…”
Section: Introductionmentioning
confidence: 99%